Physics textbooks requirements - Fürstová, Tereza; Žák, Vojtěch (Scientia in educatione, 2025)
In the context of developing a physics textbook for upper secondary schools, currently ongoing at the Department of Physics Education, Faculty of Mathematics and Physics, Charles University, the goal of this study is to answer the question: what are the requirements for physics textbooks, or more broadly for science textbooks, that repeatedly appear in studies published in international context? To address this question, a systematic search of the Web of Science database, along with content analysis and comparison of the studies found, were conducted. Especially, using various combinations of keywords, six relevant studies were identified. These studies revealed 25 recurring requirements for physics or science textbooks. Similar requirements were grouped into three main categories (and several subcategories): i) content requirements (subject-matter independent of the student, student-oriented subject matter content, student cognition, student motivation, diversity), ii) formal requirements (verbal aspects, graphical aspects), iii) structural requirements for the textbook (layout of illustrations and text, textbook organization). An extensive appendix of the article provides the original (exact) wording of the identified textbook requirements. Based on the study findings, tools will be designed to enable students, teachers, and physics education experts to evaluate the developing physics textbook. The results of the study and the developed tools will also be applicable for reflecting on other science textbooks.